2014
DOI: 10.4161/19491034.2014.990858
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolus Precursor Body (NPB): A Distinct Structure in Mammalian Oocytes and Zygotes

Abstract: Nucleoli in mammalian oocytes and zygotes, sometimes referred to as nucleolus precursor bodies (NPBs), are compact and morphologically different from nucleoli in somatic cells. We applied a unique NPB analyzing method "enucleolation" technique to zygotes to remove the NPBs. It has been reported that oocyte NPBs are essential for embryonic development; in their absence, the oocytes complete maturation and can be fertilized, but no nucleoli are formed in the zygotes and embryos, leading to developmental failure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…However, recent analysis of developmental capacities of mouse embryos obtained from enucleolated GV oocytes (Ogushi et al 2008;Ogushi and Saitou 2010) and NPB-less zygotes (Kyogoku et al 2014a(Kyogoku et al , 2014b indicated that functional and biochemical similarities between NPBs and NLBs are most likely overestimated. Indeed, embryos obtained from the enucleolated oocytes stopped development at the two-or four-cell stages, whereas enucleolated zygotes were capable of producing live pups and reconstructing normal nucleoli (Ogushi et al 2008;Ogushi and Saitou 2010;Kyogoku et al 2014aKyogoku et al , 2014b. These findings support the idea that biochemical compositions of NPBs and NLBs differ: NLBs are comprised of molecular constituents that are necessary for early embryonic development, whereas NPBs do not contain them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent analysis of developmental capacities of mouse embryos obtained from enucleolated GV oocytes (Ogushi et al 2008;Ogushi and Saitou 2010) and NPB-less zygotes (Kyogoku et al 2014a(Kyogoku et al , 2014b indicated that functional and biochemical similarities between NPBs and NLBs are most likely overestimated. Indeed, embryos obtained from the enucleolated oocytes stopped development at the two-or four-cell stages, whereas enucleolated zygotes were capable of producing live pups and reconstructing normal nucleoli (Ogushi et al 2008;Ogushi and Saitou 2010;Kyogoku et al 2014aKyogoku et al , 2014b. These findings support the idea that biochemical compositions of NPBs and NLBs differ: NLBs are comprised of molecular constituents that are necessary for early embryonic development, whereas NPBs do not contain them.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, by modification of standard immunostaining assays it has been shown that zygotic NPBs, like oocyte NLBs, contain nucleolar proteins NPM1 (B23, nucleophosmin), C23 (nucleolin) and fibrillarin but apparently lack the RNA polymerase I cofactor UBF (Fulka and Langerova 2014;Shishova et al 2015). These observations support the above-mentioned idea but they do not explain why microsurgical removal of zygotic NPBs does not affect further embryonic development (Kyogoku et al 2014a;2014b), whereas enucleolated GV oocytes are incapable of giving rise to fully developed embryos (Ogushi et al 2008;Ogushi and Saitou 2010).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The nucleolus is another vital consideration, with the presence of a structure called the nucleolus precursor body (which has structural differences from the somatic cell nucleolus) being a necessary component of the oocyte in order for successful embryonic development (Kyogoku et al . ).…”
Section: De‐extinction Through Artificial Reproductive Technologiesmentioning
confidence: 97%
“…Centromeres are also vital components of chromosomes for replication, but even the sequencing of these regions is difficult (Hayden & Willard 2012) and the assembly of the proteins that comprise this region constitutes another barrier (Aldrup-Macdonald & Sullivan 2014). The nucleolus is another vital consideration, with the presence of a structure called the nucleolus precursor body (which has structural differences from the somatic cell nucleolus) being a necessary component of the oocyte in order for successful embryonic development (Kyogoku et al 2014).…”
Section: Synthetic Genomesmentioning
confidence: 99%